Teachers’ Practices in Implementing Project-Based Learning in Early Childhood English Classrooms - Siska, Widia (BOCAH: Borneo Early Childhood Education and Humanity Journal, 2026)
The purpose of this study is to describe variations in early childhood teachers’ practices in English project-based learning (PjBL), analyze the advantages of implementing PjBL, and determine students’ English abilities after teachers implemented PjBL. This study used a qualitative descriptive approach. Participants were three English teachers at TK IT AL IRSYAD Koto Baru, Dharmasraya Regency. Data were collected through observations, interviews, and documentation. The results showed that the teachers implemented six PjBL stages: (1) planning, (2) determining the assessment rubric, (3) designing the schedule, (4) monitoring, (5) assessment, and (6) evaluation. Five advantages were identified: increased motivation, stronger critical thinking, improved teamwork, enhanced creativity, and better English ability. Finally, after PjBL implementation, students achieved good English performance, classified as BSB (very well developed). These findings indicate that structured projects can guide teachers in delivering meaningful English activities and provide clear criteria for evaluating progress in kindergarten learners in this setting.